In the smaller scope of conscience : the struggle for national repatriation legislation, 1986-1990 - McKeown, C. Timothy, 1955- (University of Arizona Press, 2013)
"In 1989, The National Museum of the American Indian Act (NMAIA) was successfully passed after a long and intense struggle. One year later, the Native American Graves Protection and Repatriation Act (NAGPRA) followed. These federal repatriation statutes--arguably some of the most important laws in the history of anthropology, museology, and American Indian rights--enabled Native Americans to reclaim human remains, funerary objects, sacred objects, and objects of cultural patrimony. Twenty years later, the controversy instigated by the creation of NMAIA and NAGPRA continues to simmer. In the Smaller Scope of Conscience is a thoughtful and detailed study of the ins and outs of the four-year process behind these laws. It is a singular contribution to the history of these issues, with the potential to help mediate the ongoing debate by encouraging all sides to retrace the steps of the legislators responsible for the acts. Few works are as detailed as McKeown's account, which looks into bills that came prior to NMAIA and NAGPRA and combs the legislative history for relevant reports and correspondence. Testimonies, documents, and interviews from the primary players of this legislative process are cited to offer insights into the drafting and political processes that shaped NMAIA and NAGPRA. Above all else, this landmark work distinguishes itself from earlier legislative histories with the quality of its analysis. Invested and yet evenhanded in his narrative, McKeown ensures that this journey through history--through the strategies and struggles of different actors to effect change through federal legislation--is not only accurate but eminently intriguing"--